Optimalisasi Pemanfaatan Daun Kelor (Moringa oleifera) melalui Pelatihan Pembuatan Sabun Mandi Herbal bagi Masyarakat - ferniawan ferniawan; Heriyanto; Adfal Anif (Postgraduate Program, University of Mataram, 2026)
Moringa oleifera is a local plant that contains various bioactive compounds with considerable potential for development into herbal-based personal care products. However, its utilization in the community has remained limited, particularly for value-added products such as herbal bath soap. This community service activity aimed to improve the knowledge and practical skills of science teachers in Mataram City regarding the production of herbal bath soap from Moringa oleifera leaves while promoting the utilization of local resources as learning media and entrepreneurial products. The program was conducted at Hotel Lombok Raya, Mataram, involving 62 junior and senior high school science teachers. A participatory training approach was employed through lectures, demonstrations, hands-on practice, discussions, and evaluations using pre-test, post-test, observation sheets, and participant satisfaction questionnaires. The results indicated a substantial improvement in participants' knowledge, with the average score increasing from 60.8% in the pre-test to 89.7% in the post-test. Practical skill assessment also showed excellent performance, with an average achievement of 93.9%, while participant satisfaction reached 97.2%. The training successfully enhanced participants' competence in producing herbal bath soap and broadened their understanding of the educational and economic potential of Moringa oleifera. It was concluded that participatory training effectively strengthened teachers' knowledge and practical skills while encouraging the integration of local resource utilization into science learning and school-based entrepreneurship activities.